The Expansion of Theatrical Space and the Role of the Spectator - Pérez, Elena (Nordic Theatre Studies, 2014)
One of the theatre and performance conventions that has been challenged by the application of technology is that of space. Theatrical space has been “expanded” through the application of technology and its artefacts. However, it is not really clear what is meant by “expansion”, as it means different things according to different authors and these divergent meanings often lead to misunderstandings. In this article, I will demonstrate the need for a more nuanced understanding of what the expansion of theatrical space means and its impact on the concept of spectatorship. The analysis will be based on three distinct forms of digital performance where spatial expansion has been an issue; these are three categories that also mark the heterogeneity and dynamism of the convergence of performance and technology: multimedia performance, telematic performance and pervasive performance. Through an analysis of specific cases across the categories, I aim to show how the expansion of space implies a more participatory stance in the role of the spectator.